Perspektif Hukum Islam terhadap Pasar Modal Syariah Sebagai Alternatif Investasi Bagi Investor - Diana Wiyanti (Jurnal Hukum IUS QUIA IUSTUM, 2013)
The Islamic economic-social life including investment cannot be separated from Sharia principles. In capital market of Sharia, the activity to gaining wealth is always accompanied with the ways of remembering Allah SWT. This research is to analyze the concept of investment in accordance with Islamic laws; thus making it possible to observe the differences between investment and speculation based on Sharia. In addition, it is also to find out the perspective of Islamic laws towards the Sharia capital market. This research uses a descriptive-analytical method with judicial-normative approach in which the analysis is qualitatively done. The result of the research then shows that in the Sharia investment, the benefits for both the world and the hereafter are having the core priority in order to make the long-term investment. Meanwhile, speculation functions are merely to obtain a short-term profit without considering any other people’s interest and mostly with the ways of breaking the accepted regulations. Islamic law highly supports the activities in Sharia capital market. This also is supported by the fundamental concept of Islamic law in Al Qur’an, Hadith, Fiqh and opinions of clergies.